Role of soil parameters in forest clove (Syzygium obtusifolium) habitat and their effects on phenology and production - MARWAN YANI KAMSURYA; SAMIN BOTANRI; KAMARUDDIN KAMARUDDIN; FAUZIA HULOPI; MUIMUNA LAHABI; JUNI LA DJUMAT (Society for Indonesian Biodiversity, 2023)
Abstract. Kamsurya MY, Bontari S, Kamaruddin, Hulopi F, Lahabi M, Djumati JL. 2023. Role of soil parameters in forest clove (Syzygium obtusifolium) habitat and their effects on phenology and production. Biodiversitas 24: 4910-4918. Forest cloves (Syzygium obtusifolium L.) are a type of non-aromatic clove that originally grew wild and are now starting to be cultivated. This study aimed to examine role of soil chemical and physical parameters in clove plant habitat and their influence on flowering phenology and production. The experiment was carried out on the island of Ambon Maluku, for a duration of 17 months from January 2020 - May 2021. A survey was conducted on forest clove plant cultivated by farmers aged between 10-15, and five observation locations were selected using the purposive sampling method. Soil analysis was performed at the Laboratory of Soil Science, Faculty of Agriculture, University of Hasanuddin Makassar, while observational data were analyzed using principal component regression analysis (PCRA). The results showed that soil chemical parameters contributed 14.89% to forest clove plant habitat, with the N and Ca content providing the highest contribution of 3.49% and 3.26% respectively. The contribution of physical parameters amounted to 8.09%, with sand particles exhibiting the highest value of 2.43%. Furthermore, PCRA results found that soil chemical parameters influenced the phenology of forest clove flowering by 21.8%. The relationship between the independent variables (X1 to X5) and flowering phenology (Y) had a correlation (R) of 0.47, while the physical parameters exerted an influence reaching 79.4% with an R-value of 0.89. The average production of fresh and dry clove flowers from forest clove plant was 50.3 and 20.1 kg/plant, respectively.